2022
DOI: 10.1038/s41433-022-01947-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of temporal artery ultrasound versus biopsy in the diagnosis of giant cell arteritis

Abstract: BACKGROUND/OBJECTIVES: Giant cell arteritis (GCA) is a medical and ophthalmological emergency due to risk of stroke and sudden irreversible loss of vision. Fast and accurate diagnosis is important to prevent complications and long-term high dose glucocorticoids toxicity. Temporal artery biopsy is gold standard for diagnosing GCA. However, temporal artery ultrasound is a fast and non-invasive procedure which may provide a supplement or an alternative to biopsy. This study assesses the diagnostic performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…In another study, pooled results reported the halo sign the sensitivity and specificity of hypoehoic halo compared with positive temporal artery biopsy were 68% and 81%, respectively. 44 In patients not receiving immunosuppressive therapy, the diagnostic accuracy of PET in detecting large-vessel involvement was significantly higher (93.3 vs 64.5%). 55…”
Section: Color Duplex Sonographymentioning
confidence: 93%
See 1 more Smart Citation
“…In another study, pooled results reported the halo sign the sensitivity and specificity of hypoehoic halo compared with positive temporal artery biopsy were 68% and 81%, respectively. 44 In patients not receiving immunosuppressive therapy, the diagnostic accuracy of PET in detecting large-vessel involvement was significantly higher (93.3 vs 64.5%). 55…”
Section: Color Duplex Sonographymentioning
confidence: 93%
“…This sign has variable size ranging from .7 to 2 mm and is specific for the diagnosis of GCA. [41][42][43][44] The lack of halo sign can basically exclude the diagnosis of GCA and lead to a reduction of an unnecessary biopsy performance. 45 Color duplex sonography is an inexpensive, non-invasive, and easy-to-perform method, allows a directional biopsy that has an increased probability to confirm the clinical diagnosis.…”
Section: Color Duplex Sonographymentioning
confidence: 99%
“…A diagnosis of either definite GCA or definite non-GCA were given by reviewing the results of symptoms, examination findings, medication, blood biochemical measurements, and diagnostic tests which could be a combination of vascular ultrasound, 18-fluorodeoxyglucose positron emission tomography, and/or TAB. Uncertain cases were discussed between specialists until consensus [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ultrasound false negative rate was 4 in 78 (5%). Therefore, the sensitivity of ultrasound is almost on par with that of biopsy, although the overall diagnostic accuracy of ultrasound was somewhat lower [8].…”
Section: Main Clinical Findingsmentioning
confidence: 97%